1988
DOI: 10.1210/jcem-66-4-798
|View full text |Cite
|
Sign up to set email alerts
|

Serum Inhibin Levels in Polycystic Ovary Syndrome: Basal Levels and Response to Luteinizing Hormone-Releasing Hormone Agonist and Exogenous Gonadotropin Administration*

Abstract: Serum inhibin levels were measured by RIA twice weekly for 4 weeks in 5 women with the polycystic ovary syndrome (PCOS). These were compared to those in 10 women with normal menstrual cycles. Serum inhibin levels were similar in the 5 PCOS women (mean, 199; range, 126-266 U/L) and were not significantly different from those in the normal women during the early follicular phase (227; 100-485 U/L) or midfollicular phase (243; 143-412 U/L) of their cycles. Inhibin levels were higher (P less than 0.001) in the lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
1
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 20 publications
4
22
1
1
Order By: Relevance
“…Some authors reported raised concentrations of total immunoreactive inhibins [19], α-inhibin [9,13] or inhibin B [20,21,22], supporting the above hypotheses, while others observed normal levels of total immunoreactive inhibin [12] or inhibin B [1,10,13,23] in the early follicular phase.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Some authors reported raised concentrations of total immunoreactive inhibins [19], α-inhibin [9,13] or inhibin B [20,21,22], supporting the above hypotheses, while others observed normal levels of total immunoreactive inhibin [12] or inhibin B [1,10,13,23] in the early follicular phase.…”
Section: Introductionmentioning
confidence: 73%
“…Decreased inhibin concentrations during the midluteal phase may be at least in part responsible for impaired corpus luteum function often present in PCOS. However, to the best of our knowledge, only total immunoreactive inhibin levels have been compared in the second half of the menstrual cycle between PCOS patients and normal controls [12].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have evaluated the hypothesis that the endocrine or paracrine influence of inhibin might be enhanced in PCOS. However, these studies were performed by measuring either ␣-inhibin or dimeric inhibin, and generally did not find a difference in serum inhibin levels between control women and PCOS patients (25)(26)(27), with one exception (28). In these studies no relationship between either serum androgen or FSH and inhibin levels in PCOS women was noted.…”
Section: Nhibins Are Dimeric Glycoproteins Consisting Of Anmentioning
confidence: 91%
“…E2 during ovulation induction in normal women [7][8][9] or women with polycystic ovarian syndrome [10], and indeed a significant correlation between the two hormones was shown in women undergoing ovulation induction by pFSH [15]. However these findings were obtained under conditions where the effect of endogenous LH was present.…”
Section: Studymentioning
confidence: 93%
“…Both hormones are produced and released by the granulosa cells during the menstrual cycle [3][4][5][6]. In fact a parallel increase in the two hormones in response to exogenous gonadotropin has been demonstrated in normal women [7][8][9] and in amenorrheic women with polycystic ovarian disease (PCOD) [10]. These reports indicate that measurement of inhibin can be a useful marker for evaluating granulosa cell function [6] or predicting the clinical outcome of the treatment [7][8][9], but there is still a lack of knowledge of inhibin secretion during ovulation induction.…”
mentioning
confidence: 99%